A Structural Equation Decision Model for ATM Cash Management and Routing: Balancing Cost and Customer Satisfaction in the Banking Sector - Ramiz Assaf; Abdalmuttaleb Al-Sartawi; Zaher Abusaq; Mohammad Kanan (Decision Making: Applications in Management and Engineering, 2025)
This research explores the factors influencing ATM cash management and routing efficiency within the Palestinian banking industry, employing responses from 500 banking personnel and analysing the data using Partial Least Squares Structural Equation Modelling (PLS-SEM). The conceptual framework incorporates managerial competence, technological readiness, and both regulatory and environmental support as antecedents of operational performance and customer satisfaction. The findings indicate that these organisational elements significantly contribute to enhanced operational performance, which subsequently acts as a mediator in improving customer satisfaction. While cost management effectiveness does not exert a direct influence on satisfaction, it slightly moderates and strengthens the association between operational performance and satisfaction. This study contributes to the literature by integrating behavioural insights with operational outcomes and offers practical guidance for financial institutions and regulatory bodies aiming to enhance ATM-related services and customer value in developing economies.